Efficacy of the porcine species in biomedical research - Gutierrez, Karina; Dicks, Naomi; Glanzner, Werner G.; Agellon, Luis B.; Bordignon, Vilceu (Frontiers in Genetics, 2015)
Since domestication, pigs have been used extensively in agriculture and kept as companion animals. More recently they have been used in biomedical research, given they share many physiological and anatomical similarities with humans. Recent technological advances in assisted reproduction, somatic cell cloning, stem cell culture, genome editing and transgenesis now enable the creation of unique porcine models of human diseases. Here we highlight the potential applications and advantages of using pigs, particularly minipigs, as indispensable large animal models in fundamental and clinical research, including the development of therapeutics for inherited and chronic disorders, and cancers.